Perceraian pada Masa Pandemi di Pengadilan Agama Kota Bandung Perspektif Maslahah Mursalah - Wafa Qurota Aini; Yandi Maryandi; Muhammad Yunus (Jurnal Riset Hukum Keluarga Islam, 2023)
Abstract. In the household there are various things that can cause disputes, leading to divorce, especially during the Covid-19 pandemic, which is one of the causes of the increasing number of divorces in the Bandung Religious Court due to various factors. Maslahah mursalah is one of the theories of extracting law in Islam when there are no rules in the Qur'an or hadith. Researchers in their research formulated the following problem formulation: How is divorce law in Islam; What is the divorce rate during the Covid 19 pandemic in the city of Bandung; What is the impact of divorce during the covid 19 pandemic at the Bandung City Religious Court from the perspective of maslahah mursalah; As for the purpose of this study is to answer the formulation of the problem. This research is a field research, using an empirical juridical approach. The results of his research are that in Islam divorce talak is a divorce in which the husband submits a divorce application to the Religious Court, while the wife seeks divorce; Divorce cases during the Covid 19 pandemic at the Bandung City Religious Court have increased. And the impact of divorce during the Covid 19 pandemic at the Bandung Religious Court was in accordance with the maslahah mursalah by considering the reasons and factors for divorce to avoid harm and bring benefit. Abstrak. Dalam rumah tangga terdapat berbagai hal yang dapat menyebabkan perselisihan, hingga menimbulkan perceraian terlebih pada masa pandemi covid-19 yang menjadi salah satu penyebab meningkatnya angka perceraian di Pengadilan Agama Bandung karena berbagai faktor. Maslahah mursalah merupakan salah satu teori penggalian hukum dalam Islam ketika tidak ada aturan dalam Al-Qur’an maupun hadist. Peneliti dalam penelitiannya merumuskan rumusan masalah sebagai berikut: Bagaimana hukum perceraian dalam islam; Bagaimana tingkat perceraian di masa pandemi covid 19 di Kota Bandung; Bagaimana dampak perceraian pada masa pandemic covid 19 di Pengadilan Agama Kota Bandung perspektif maslahah mursalah; adapun tujuan dari penelitian ini yaitu menjawab rumusan masalah. Penelitian ini merupakan penelitian lapangan (field research), menggunakan pendekatan yuridis empiris. Hasil penelitiannya bahwa dalam islam cerai talak yaitu perceraian yang diajukan permohonan cerainya oleh suami ke Pengadilan Agama sedangkan cerai gugat diajukan oleh istri; kasus perceraian pada masa pandemic covid 19 di Pengadilan Agama Kota Bandung mengalami peningkatan. Dan dampak dari perceraian pada masa pandemic covid 19 di Pengadilan Agama Bandung sudah sesuai dengan maslahah mursalah dengan mempertimbangkan alasan dan faktor perceraian untuk menghindari kemadharatan dan mendatangkan kemaslahatan.